Air-thermal oxidation of zirconium materials - Pylypenko, M.M.; Drobyshevskaya, A.A.; Stadnik, Yu.S.; Tantsyura, I.G. (Вопросы атомной науки и техники, 2014)
The results of the temperature effect on the process of oxide films formation on the surface of the zirconium materials are given. The changes of the morphology, structure and properties of the oxide films on the zirconium and Zr1%Nb alloy due to exposure of heat treatment in air at 500…800 ºС for a time up to 10 h are analyzed. Приведены результаты исследований влияния температуры на процесс образования оксидных пленок на поверхности циркониевых материалов. Проанализированы изменения морфологии, структуры и свойств оксидных пленок на цирконии и сплаве Zr1%Nb в результате воздействия термической обработки в воздуш- ной среде при 500…800 ºС в течение 10 ч. Приведено результати досліджень впливу температури на процес утворення оксидних плівок на поверхні цирконієвих матеріалів. Проаналізовано зміни морфології, структури і властивостей оксидних плівок на цирконії та сплаві Zr1%Nb в результаті впливу термічної обробки в повітряному середовищі при 500…800 ºС протягом 10 год.